Advances in digital cultural heritage : International Workshop, Funchal, Madeira, Portugal, June 28, 2017, Revised selected papers /: International Workshop, Funchal, Madeira, Portugal, June 28, 2017, Revised selected papers. (2018) - Unknown
No abstract available